Rectal Polyp Prolapse: A Case Report - Agarwal, Nirmal Kumar; Nath Choudhury, Dhirendra; Minocha, Akshit (Asian Pacific Journal of Cancer Biology, 2023)
Colorectal adenomas are polyps that develop from the mucosa and exhibit neoplastic characteristics. Adenomas’ increasing dysplasia and malignant potential are connected to their size, villous content, and patient’s age. An anorectal emergency is definitely a possibility when there are large villous polyps in the rectum. They could be involved in rectal bleeding, blockage, prolapse, or imprisonment. We describe a 53-year-old female who was treated successfully for giant tubulovillous rectal adenoma that was prolapsed through anal opening. The patient’s clinical symptoms and signs were mistaken for prolapsed hemorrhoids.